(untitled) (Journal of Science and Technology, 2016)
The urgent need for the HIV/AIDS pandemic to be tackled at the workplace cannot be overemphasized given the internal and external impacts it has on businesses. This led to the formulation of the National HIV/AIDS Workplace Policy to be replicated by companies especially the private sector which is the engine of growth. A sample of 155 private companies (five with HIV/AIDS workplace policy and 150 without the policy) in the Western Region was selected for comparative analysis through interviews using the purposive, cluster and simple random sampling techniques. The results indicated that the knowledge levels of managers of private companies on HIV/AIDS issues and their appreciation of the impact of the pandemic would influence the quantum of resources to be committed to reduce the prevalence rate. Thus, the formulation and implementation of HIV/AIDS workplace policies could lead to an increase in the knowledge levels of both workers and managers and it is hoped that in the long run, it would result in a reduction in the prevalence levels.